Harnessing the power of stories: Evaluating complex tourism interventions through a ‘most significant change’ approach - Luigina Jessica Montano; Xavier Font; Corinna Elsenbroich; Manuel Alector Ribeiro (Annals of Tourism Research Empirical Insights)
This study explores the power of the story-based ‘Most Significant Change’ evaluation method to evidence the impacts of a complex sustainable tourism intervention implemented through the cross-border EU-INTERREG ‘EXPERIENCE’ project across six regions on the French-English Channel. The method provides a participatory evaluation framework to capture contextual changes by collecting and analysing personal stories of change considered significant by those directly affected. As intervention-driven changes are often unpredictable and non-linear, the method supports researchers in exploring and learning about unexpected or complex outcomes emerging from the stories. Findings highlight the effectiveness of this narrative approach in capturing complex, unforeseen changes that may not be quantifiable through pre-defined performance indicators. The study contributes to evaluating EU-funded regional development programmes in tourism.